Construire l’interopérabilité culturelle autour de la documentation et de l’information dans une communauté de pratique - Karel Soumagnac-Colin (Communication)
Based on her analysis of the professional management of the French green building industry, the author identifies issues of cultural interoperability for managers and shows the difficulties they experience in generating an interoperable system for working together. She begins by explaining the notion of cultural interoperability within a community of practice. She then presents the methodology and results of her research, which represent a step forward in developing the prospective aspects of an intercultural platform.